2019
DOI: 10.3390/cli7010013
|View full text |Cite
|
Sign up to set email alerts
|

Can Protection Motivation Theory Explain Farmers’ Adaptation to Climate Change Decision Making in The Gambia?

Abstract: In The Gambia, climate change has affected, and continues to affect, the agriculture sector. Thus, there is a need to develop and understand effective agricultural adaptation policies. The present study used protection motivation theory to describe farmers’ adoption of climate change adaptation measures in the Central River Region of The Gambia. Primary data were collected in eight communities of the region. A transect walk was conducted, followed by a survey of farmers (n = 283). Perception data collected ref… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 35 publications
1
16
0
Order By: Relevance
“…The protection motivation theory (PMT) was first introduced by Rogers in 1975, in order to understand individual's response to potential threats of health problem. Later Rogers (1975) extended its iteration to other social science issues including environmental concern (Bagagnan, Ouedraogo, Fonta & Sowe, 2019). The theory proposes a conceptual framework to explain factors predicting risk preventative behaviors.…”
Section: Protection Motivation Theory (Pmt)mentioning
confidence: 99%
“…The protection motivation theory (PMT) was first introduced by Rogers in 1975, in order to understand individual's response to potential threats of health problem. Later Rogers (1975) extended its iteration to other social science issues including environmental concern (Bagagnan, Ouedraogo, Fonta & Sowe, 2019). The theory proposes a conceptual framework to explain factors predicting risk preventative behaviors.…”
Section: Protection Motivation Theory (Pmt)mentioning
confidence: 99%
“…They only apply it when they expect favorable weather conditions so that they will improve their productivity. Similar studies have found that farmers' perception of climate change can determine their adaptation options [41,43].…”
Section: Discussionmentioning
confidence: 65%
“…There is also the cost associated with current water conservation techniques, which is not always affordable for most farmers. The cost was found to be a significant barrier to farmers' adoption of climate change adaptation measures [41,42]. The correlation analysis showed a significant relationship between some perception variables and farmer-stated implementation of the adaptation measures.…”
Section: Discussionmentioning
confidence: 99%
“…The protection motivation theory (PMT) was first introduced by Rogers in 1975 with the main purpose of assessing individual's response to perceived threats of health problems and motivation to respond to the threats. Later, it is extended to other social science issues such as environmental degradation and response measures (Bagagnan et al, 2019). The theory sheds light on factors influencing individual's motivation to react to a perceived risk.…”
Section: Protection Motivation Theorymentioning
confidence: 99%
“…Consequently, compared to other, strategies such as soil conservation and agricultural intensification, irrigation and fuel wood conservation are less practiced by the farmers. Farmers' subjective understanding of changes in the climate positively influences their protection motivation, while the cost of adaptation measures negatively affects their protection motivation (Bagagnan et al, 2019).…”
Section: Determinants Of Climate Change Mitigation and Adaptation Strmentioning
confidence: 99%